Theleetops.my / Anis Nurkhalidah Ahmad Fazil - Ahmad Fazil, Anis Nurkhalidah (2021)
Theleetops.my’s tagline is "Born to Lit with Style," and the #leetopsdewi hashtag represents our loyal clients. The major goal for this business is to provide high-quality hijabs in a range of various designs at inexpensive and reasonable price range costs that are ready to wear on our beloved customers. On April 27th, 2020, we launched our digital business on the social media platform. Students, workers, ladies, and men are our target audience especially to people who are working or studying around the universities and schools. Since our first day, we have had a lot of positive feedback from customers on the hijab's quality, comfort, and the feeling of wearing them on their heads. We provided a fee-based delivery service to people who lived close by. We also provide a mystery box for those customers who want to surprise their loved ones or even themselves. This is one of our marketing strategies to entice more customers to visit our store and purchase our goods. Over 100 pieces of Bawal Eyelash and 200 pieces of Shawl from theleetops.my were sold. Hence, this is a good sign that our goods are being accepted among the marketplace.